DETEKSI DINI STUNTING PADA BAYI DAN BALITA DI WILAYAH KERJA PUSKESMAS PEGAMBIRAN KOTA PADANG - Yusrawati Yusrawati; Desmawati Desmawati; Arni Amir; Joserizal Serudji; Vaulinne Basyir; Hudilla Rifa Karmia; Aldina Ayunda Insani; Miranie Safaringga; Lisma Evareny (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2022)
Nutritional status has a significant influence on the growth and development of children. Poor nutrition during the first 1000 days of life (HPK) can reduce the risk of disease, one of which is stunting, as well as the risk of death, which is around 13% (WHO, 2009). In 2018 the percentages of very short and short toddlers aged 0-59 months were 11.5% and 19.3%, respectively. The magnitude of the risk of stunting for infants and toddlers, it is necessary to hold early detection of stunting as an effort to help increase knowledge that is implemented in monitoring activities for growth and development of infants and toddlers that are more optimal. The activity was carried out on November 18, 2021 with 20 mothers who have babies and toddlers. This group was given counseling, physical examination and early detection of growth and development using the KPSP questionnaire. The results showed that 6.25% of underweight infants and 6.25% of obese infants, 44% of infants and toddlers in the short category, 6% very short, 81% of exclusive breastfeeding, 6% of infants with deviations (smooth motion, socialization and independence) and 6 % of dubious results (rough motion). It is hoped that husbands, families and the community will monitor the growth and development of infants and toddlers to prevent stunting and other growth and development disorders. Health workers should always promote balanced nutrition programs and other stuntin prevention efforts since the preparation for pregnancy (preconception).